Five new species and a new record of Sathytes Westwood from eastern China (Coleoptera: Staphylinidae: Pselaphinae) - Shen, Qi; Yin, Zi-Wei (Zootaxa, 2020)
The known Chinese fauna of the genus Sathytes Westwood (Pselaphinae: Batrisini) is comprised of 15 species. Here we describe five more species from eastern China: S. communis Shen & Yin, sp. nov. (from Anhui, Zhejiang and Jiangxi), S. fenghuang Shen & Yin, sp. nov. (from Zhejiang), S. jinggang Shen & Yin, sp. nov. (from Jiangxi), S. obliquus Shen & Yin, sp. nov. (from Zhejiang), and S. similis Shen & Yin, sp. nov. (from Zhejiang and Jiangxi). Moreover, Sathytes larinus Yin & Li, originally known from Fujian, is newly recorded from Zhejiang.